Body composition by bioelectrical impedance analysis in children below 7 years old - Jiyoung Jung; Han Wool Kim; Tae Hyun Kim; Young Mi Hong (Korean Pediatric Society, 2010)
Purpose : Body composition is important to define and manage obesity and undernutrition. Obesity is a significant health problem with medical and psychological consequences for children and adolescents. Body composition analysis (BIA) is a simple, rapid, noninvasive, and reproducible technique. However, comparative analysis of body composition has not been done in young children below 7 years old. The aim of this study is to estimate antropometric data and body composition by BIA, and to investigate the correlation between anthropometric data and fat mass or fat percent in young children. Methods : We measured height, weight, body mass index (BMI), fat mass, and fat percent by BIA in 1,376 children aged 3–6 years of whom 688 were males and 688 were females. Results : Fat mass, fat percent, intracellular fluid, extracellular fluid, protein, and minerals were significantly higher in the obese group. A significant positive correlation exists between fat mass and BMI or weight. A significant positive linear correlation was also noted between fat percent and BMI. Protein, weight, fat mass, and fat percent were significantly different among groups. Conclusion : BIA is an objective, accurate method to estimate body fat in childhood obesity cases. Fat mass and fat percent data acquired by using BIA highly correlated with BMI. However, a large-scale study is needed to diagnose obesity in young children.